Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1038/nmicrobiol.2017.98
|View full text |Cite
|
Sign up to set email alerts
|

HBV RNA pre-genome encodes specific motifs that mediate interactions with the viral core protein that promote nucleocapsid assembly

Abstract: Formation of the Hepatitis B (HBV) nucleocapsid (NC) is an essential step in the viral lifecycle but its assembly is not fully understood. We report the discovery of sequence-specific interactions between the viral pre-genome and HBV core protein (Cp) that play roles in defining the NC assembly pathway. Using RNA SELEX and bioinformatics we identified multiple regions in the pre-genomic RNA with high-affinity for Cp dimers. These RNAs form stem-loops with a conserved loop motif that trigger sequence-specific a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
140
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(146 citation statements)
references
References 60 publications
4
140
0
Order By: Relevance
“…3F and 4G). This result demonstrates that few, if any, small conserved RNA structures exist in the P2 and P3 regions of the analyzed viruses that could accommodate the hypothesis of "multiple cryptic, sequence-degenerate, dispersed RNA packaging signals" (22). Manual inspection of structures conserved after synonymous recoding revealed that the majority of prevailing structures occurred over regions encoding amino acids that had reduced codon choice, such that selection of any possible synonymous codon would conserve the presence or absence of base-pairing.…”
Section: Resultsmentioning
confidence: 81%
See 4 more Smart Citations
“…3F and 4G). This result demonstrates that few, if any, small conserved RNA structures exist in the P2 and P3 regions of the analyzed viruses that could accommodate the hypothesis of "multiple cryptic, sequence-degenerate, dispersed RNA packaging signals" (22). Manual inspection of structures conserved after synonymous recoding revealed that the majority of prevailing structures occurred over regions encoding amino acids that had reduced codon choice, such that selection of any possible synonymous codon would conserve the presence or absence of base-pairing.…”
Section: Resultsmentioning
confidence: 81%
“…Each conserved structure is represented by a rectangle that spans the range of the structure's position. (22). These hairpins, which are loosely conserved and carry common "assembly motifs," have been shown in in vitro experiments to promote RNA-dependent assembly of viral capsids, including elaborate structural rearrangements of capsid subunits (refs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations